1994
DOI: 10.1111/j.1399-3054.1994.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soybean to ammonium and nitrate supplied in combination to the whole root system or separately in a split‐root system

Abstract: To address the questions of whether allocation of carbohydrates to roots is influenced by ionic form of nitrogen absorbed and whether allocation of carbohydrates to roots in turn influences proportionality between NH4+ and NO3- uptake from mixed sources, NH4+ and NO3- were supplied separately to halves of a split-root hydroponic system and were supplied in combination to a whole-root system. Dry matter accumulation in the split-root system was 18% less in the NH4(+)-fed axis than in the NO3(-)-fed axis. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Many studies have shown that when roots are supplied a moderate N concentration completely by sole NH 4 + nutrition, the growth of roots, shoots, and even fruits is usually significantly inhibited (Schortemeyer et al 1997;Zou et al 2005;Claussen 2002;Wang et al 2003;Chaillou et al 1994;Feil 1994). However, if the roots were spatially half supplied with sole NH 4 + and half with sole NO 3 − , roots in the sole NH 4 + part suffered from depressed growth (Guo et al 2002(Guo et al , 2007Chaillou et al 1994), whereas the shoots were still able to accumulate a high dry matter (DM) content. This indicates that plants have the ability to control development at a whole-plant level (Gansel et al 2001) to adapt themselves to environments with uneven N-distribution (Zhang and Forde 1998).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have shown that when roots are supplied a moderate N concentration completely by sole NH 4 + nutrition, the growth of roots, shoots, and even fruits is usually significantly inhibited (Schortemeyer et al 1997;Zou et al 2005;Claussen 2002;Wang et al 2003;Chaillou et al 1994;Feil 1994). However, if the roots were spatially half supplied with sole NH 4 + and half with sole NO 3 − , roots in the sole NH 4 + part suffered from depressed growth (Guo et al 2002(Guo et al , 2007Chaillou et al 1994), whereas the shoots were still able to accumulate a high dry matter (DM) content. This indicates that plants have the ability to control development at a whole-plant level (Gansel et al 2001) to adapt themselves to environments with uneven N-distribution (Zhang and Forde 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that plants have the ability to control development at a whole-plant level (Gansel et al 2001) to adapt themselves to environments with uneven N-distribution (Zhang and Forde 1998). To our knowledge, although there are some comparisons of shoot and root growth responding to both homogeneous and localized supply of different N forms in tobacco and soybean plantlets (Walch-Liu et al 2000;Chaillou et al 1994), few reports have described differences in root morphology in response to different NO 3 − :NH 4 + ratios under either homogeneous or split-root systems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations